Mobilization of intensive care patients: a multidisciplinary practical guide for clinicians - Green M; Marzano V; Leditschke IA; Mitchell I; Bissett B (Journal of Multidisciplinary Healthcare, 2016)
Margot Green1, Vince Marzano1, I Anne Leditschke2,3, Imogen Mitchell2,3, Bernie Bissett1,4,5 1Physiotherapy Department, Canberra Hospital, Canberra, ACT, Australia; 2Intensive Care Unit, Canberra Hospital, Canberra, ACT, Australia; 3School of Medicine, Australian National University, Canberra, ACT, Australia; 4Discipline of Physiotherapy, University of Canberra, Canberra, ACT, Australia; 5School of Medicine, University of Queensland, Brisbane, QLD, Australia Objectives: To describe our experience and the practical tools we have developed to facilitate early mobilization in the intensive care unit (ICU) as a multidisciplinary team.Background: Despite the evidence supporting early mobilization for improving outcomes for ICU patients, recent international point-prevalence studies reveal that few patients are mobilized in the ICU. Existing guidelines rarely address the practical issues faced by multidisciplinary ICU teams attempting to translate evidence into practice. We present a comprehensive strategy for safe mobilization utilized in our ICU, incorporating the combined skills of medical, nursing, and physiotherapy staff to achieve safe outcomes and establish a culture which prioritizes this intervention.Methods: A raft of tools and strategies are described to facilitate mobilization in ICU by the multidisciplinary team. Patients without safe unsupported sitting balance and without ≥3/5 (Oxford scale) strength in the lower limbs commence phase 1 mobilization, including training of sitting balance and use of the tilt table. Phase 2 mobilization involves supported or active weight-bearing, incorporating gait harnesses if necessary. The Plan B mnemonic guides safe multidisciplinary mobilization of invasively ventilated patients and emphasizes the importance of a clearly articulated plan in delivering this valuable treatment as a team.Discussion: These tools have been used over the past 5 years in a tertiary ICU with a very low incidence of adverse outcomes (<2%). The tools and strategies described are useful not only to guide practical implementation of early mobilization, but also in the creation of a unit culture where ICU staff prioritize early mobilization and collaborate daily to provide the best possible care.Conclusion: These practical tools allow ICU clinicians to safely and effectively implement early mobilization in critically ill patients. A genuinely multidisciplinary approach to safe mobilization in ICU is key to its success in the long term. Keywords: physiotherapy (techniques), critical care, intensive care, multidisciplinary communication